Excessive iodine intake in schoolchildren - Carvalho, Adriana Lelis; Costa de Souza Meirelles, Clarissa Janson; Oliveira, Luciana Abrao [UNESP]; Braga Costa, Telma Maria; Navarro, Anderson Marliere (Springer Heidelberg, 2012)
Inadequate iodine intake may result in iodine deficiency disorders (IDD). Thus, for more than 50 years, policies for the regulation of salt fortification with iodine have existed in Brazil. In 2003, a study on 6-14-year-old schoolchildren from regions of the state of So Paulo showed a median urinary iodine concentration of 360 mu g/L. The objective of the present study was to assess the iodine nutrition status among schoolchildren.The study was conducted on 828 schoolchildren aged 4-13 years from eight schools in the interior of the state of So Paulo. A casual urine sample was collected from each volunteer for iodine determination by the adapted method of Sandell-Kalthoff.Only 1.9% (n = 16) of the children evaluated had low values of urinary iodine (< 100 mu g/L), while 24.6% had urinary iodine excretion values between 200 and 300 mu g/L, and 67.1% had values above > 300 mu g/L.The results show that the iodine nutritional status of the schoolchildren studied is characterized by a high urinary iodine excretion, which might reveal an increase in iodine consumption by this population.
Keywords: Urinary iodine; Schoolchildren; Iodine; Salt